Тенденции развития технологий соединения материалов - фон Хофе, Д.; Миддельдорф, К. (Автоматическая сварка, 2008)
The main aspects which define the manufacture of technical products are reviewed. The characteristics to modern technologies of material joints are given concentrating on up-to-date developments. The forecast for the prospects of development of joint technologies including microjoints was made from the point of view of technical and cost efficiency.